2018
DOI: 10.22146/ijc.21156
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Transformation of Natural Zeolite from Ende-NTT and Its Application as Adsorbent of Cationic Dye

Abstract: A synthetic zeolite was produced from natural zeolite from Ende-Nusa Tenggara Timur (NTT) 17.289, 17.276, and 16.483 mg/g, respectively, and after hydrothermal they increased to 37.398, 37.369 and 37.362 mg/g, respectively. In addition, the CEC increased from 84.154, 81.042, and 77.474 cmol/kg, respectively, to 244.063, 216.354, and 211.432 cmol/kg, respectively 37,394, 37,365, dan 37,360 mg/g. Selain itu,15, 81,04, dan 77,47 cmol/kg meningkat menjadi 244,06, 216,35, dan 211,43 cmol/kg. Model Langmuir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
0
12
0
5
Order By: Relevance
“…It was found that the modification of natural zeolites could significantly increase the adsorption of MB. The unmodified natural zeolite could only adsorb as much as 16-17 mg/g of MB, and this number increase twofold (reaching 36-37 mg/g) after modification using the hydrothermal process [24]. Vezentsev et al also reported adsorption of MB using bentonite clay and hydroxyapatite, and it was found that bentonite clay could adsorb MB significantly higher than hydroxyapatite.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the modification of natural zeolites could significantly increase the adsorption of MB. The unmodified natural zeolite could only adsorb as much as 16-17 mg/g of MB, and this number increase twofold (reaching 36-37 mg/g) after modification using the hydrothermal process [24]. Vezentsev et al also reported adsorption of MB using bentonite clay and hydroxyapatite, and it was found that bentonite clay could adsorb MB significantly higher than hydroxyapatite.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Damiyine et al reported the usage of clay to adsorb RB, and the result suggested that the adsorption process preferably at higher pH with the adsorption capacity of the material reached 89.28 mg/g of RB [23]. Turning to MB, Ngapa et al reported adsorption of MB using natural zeolite (Mordenite) from Ende [24]. It was found that the modification of natural zeolites could significantly increase the adsorption of MB.…”
Section: ■ Introductionmentioning
confidence: 99%
“…the loss of bacteria biomass in the systems with high hydraulic loading rates. In the literatures, zeolites have reported shown a great capacity for adsorption of heavy metal (Mn, Cu, Cd, Pb and Zn) [13][14][15], aflatoxins [16], and cationic dye [17]. In addition, previously researchers reported that zeolites can be useful as a microbial support in anaerobic processes of different wastewaters [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the modified Ende-Flores Natural zeolite use hydrothermal method for adsorption a cationic dye have been reported 12 . They used a base solution to activate the NZ.…”
Section: Introductionmentioning
confidence: 99%